Impact of near freezing temperature storage on postharvest quality and antioxidant capacity of two apricot (Prunus armeniaca L.) cultivars. Issue 7 (14th April 2019) - Cui, Kuanbo; Zhao, Handong; Sun, Lina; Yang, Liling; Cao, Jiankang; Jiang, Weibo
Abstract: To reduce the postharvest loss and improve apricot quality attributes, near freezing temperature (NFT) technology was applied to store apricot cultivars (var. "Xiaobai" and "Daliguang"). The NFT storage temperatures for the "Xiaobai" apricot and "Daliguang" apricot were determined as −1.9 to −2.3°C and −1.2 to −1.6°C, respectively. Storage at NFT significantly improved the storage quality of apricots by suppressing respiration rate, ethylene production, decay rate, internal browning index, membrane permeability, and malondialdehyde content. Apricots stored at NFT maintained higher firmness, total soluble solids, titrable acid, total phenolics, total flavonoids, and ascorbic acid content than those stored at 0–1°C. Additionally, NFT storage enhanced the capacity of radical scavenging and metal chelating, antioxidant properties in apricots compared to those stored at 0–1°C. Hence, NFT storage proved to be an effective method to improve the quality and antioxidant attributes of apricots. Practical applications: This study explored the effect of storage at near freezing temperature (NFT) on the postharvest quality of two cultivars of apricot (var. "Xiaobai" and "Daliguang"). We found that storage for 70 days at NFT resulted in better edible quality compared to storage at 0–1°C and 4–6°C. Apricot quality was determined in terms of respiration rate, ethylene production, decay rate, internal browning index, membrane permeability, malondialdehyde content, firmness, total soluble solids, titrable acid, total phenolics, total flavonoids, and ascorbic acid content. The antioxidant properties of the fruits were also retained during storage at NFT. We believe that our study makes a significant contribution to the preservative industry because it demonstrates the superiority of NFT storage over low temperature for apricots.